The Art of Designed Environments in The Netherlands - Benjamin III, Lloyd W. (Amsterdam : Stichting Kunst en Bedrijf Amsterdam, 1983)
Alberts, Marcel ; Korvinus, Wim ; Beljon, Joop ; Berkulin, Arie ; Besemer, Theo ; Bleeker, Sies ; de Boer Lichtveld, Frans & Marja ; Boezem, Marinus ; Daan, Karin ; Marks, Harry ; Terwindt, Eugène ; Daniëls, Jan Hein ; Maters, Bas ; van Eyk, Ria ; Ficheroux, Mathieu ; Van Goethem, Jan ; de Goey, Marijke ; Hamelberg, Arnold ; van Santen, Joost ; Hendriks, Berend ; van Vuuren, Marcel ; Kaper, Carla ; Keizer, Jerry ; Koetsier, Hans ; de Kop, David van ; de Laaf, Bert ; van Munster, Jan ; Wondergem, Erik ; Marks, Harry ; van Vuuren, Marcel ; Mes, Antoine ; Meyer, Jacob ; de Nooijer, Paul ; Oxenaar, R.D.E. ; Pennock, Lon ; Terwindt,,Eugène ; Pessink, Jo ; Petri, Hans ; Röling, Wiek ; Van Roojen, Joost ; Sanders, Har ; van Santen, Joost ; Hamelberg, Arnold ; Schippers, Wim T. ; Scholten, Herman ; Snoeck, Jan ; Strobos, Evert ; Struycken, Peter ; Volten, André ; Verhoog, Aat ; Visser, Carel ; de Vries, Auke ; van der Waerden, Anne ; van Wijk, Jan ; Peter Stuyvesant Stichting Zevenaar
bibliog. p. 169-171
The Art of Designed Environments in The Netherlands, reizende expositie over kunst en omgeving. Tentoonstelling o.a. in Singer Museum, Laren, 1983 ; Washington ; Edinburgh ; ...
English
kunstcatalogus
Keywords: Nederland